LOCATION OF TB(III) IONS IN NA-Y ZEOLITE DETERMINED BY LUMINESCENCE SPECTROSCOPY - HONG, SB; SEO, JS; PYUN, CH; KIM, CH; UH, YS (BALTZER SCI PUBL BV, 1995)
The variation of the cation location and occupancy at different sites in TbNa-Y zeolites as a function of treatment temperature is monitored by luminescence spectroscopy. It is found that the spectral changes caused by thermal treatments can be qualitatively rationalized in terms of the site symmetry around the Tb(III) ion. The luminescence results demonstrate that most of the Tb(III) ions exchanged into supercages of the zeolite migrate first to sodalite cages at temperatures lower than 473 K and then migrate to hexagonal prisms between 473 and 523 K.
Keywords: RARE-EARTH IONS; CATION DISTRIBUTION; EXCHANGED-ZEOLITE; METAL; NMR; DIFFRACTION; TRANSITIONS; EU-3+